Cyberbullying in e-Learning platform: a text mining analytics - Kartiwi, Mira; Gunawan, Teddy Surya (International Conference on E-Learning 2019, 2019)
The adoption and use of Learning Management System (LMS) in Higher Education Institutions (HEIs) have become inevitable for teaching and learning process. It facilitates communications between teachers and students, as well as among students, regardless of physical barriers and time. However, there is also a dark side to the online environment, given more and more adolescents admit they have been the victims or bystanders of cyberbullying. In order to ensure that the online learning environment is safe for everyone, it is critical to assess the extent of the conversation carried out through the platform so as to ensure that no such misconduct is carried out via LMS. This paper also aimed to propose a practical solution to combat cyberbullying in an educational platform, and shed some lights on the potential applications of text mining techniques in educational research.